Stainless steel channel sections under combined compression and minor axis bending – part 2 : parametric studies and design - Liang, Yating (2020)
Following the experimental study and finite element (FE) model validation described in the companion paper, numerical parametric studies and the evaluation of design provisions for stainless steel channel sections under combined axial compressive load and minor axis bending moment are presented herein. The parametric studies were carried out to generate additional structural performance data over a wider range of cross-section aspect ratios and slendernesses, loading combinations and bending orientations. The test data and numerical results have been carefully analysed to develop a comprehensive understanding of the structural performance of stainless steel channel sections under combined compression and minor axis bending moment, and to assess the accuracy of the existing design provisions in Europe and North America. Comparisons of ultimate loads from the tests and FE simulations with the codified resistance predictions revealed that the current design standards typically under-estimate the capacity of stainless steel channel sections under combined compression and minor axis bending moment; this is attributed primarily to the neglect of material strain hardening and the employment of conservative interaction formulae. Improved design rules featuring more efficient interaction curves, anchored to more precise end points (i.e. cross-section resistances under pure compression and bending moment), are then proposed and presented. The new design proposals are shown to yield both more accurate and more consistent resistance predictions over the existing design provisions. Finally, statistical analyses are presented to confirm the reliability of the new design proposals according to EN 1990.